2019
DOI: 10.7554/elife.47454
|View full text |Cite
|
Sign up to set email alerts
|

The mechanosensitive Piezo1 channel is required for bone formation

Abstract: Mechanical load of the skeleton system is essential for the development, growth, and maintenance of bone. However, the molecular mechanism by which mechanical stimuli are converted into osteogenesis and bone formation remains unclear. Here we report that Piezo1, a bona fide mechanotransducer that is critical for various biological processes, plays a critical role in bone formation. Knockout of Piezo1 in osteoblast lineage cells disrupts the osteogenesis of osteoblasts and severely impairs bone structure and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
263
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 276 publications
(310 citation statements)
references
References 46 publications
(72 reference statements)
15
263
0
Order By: Relevance
“…PIEZO1 can also regulate the cell fate determination of mesenchymal stem cells in response to hydrostatic pressure (Sugimoto, 2017). Knockout of PIEZO1 in osteoblasts and osteocytes blunts the skeletal response to mechanical loads and resulted in the impair of bone structure and strength (Li et al, 2019; Sun et al, 2019). And PIEZO1 agonist could increase bone mass in adult mice, simulating the effects of mechanical loading (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…PIEZO1 can also regulate the cell fate determination of mesenchymal stem cells in response to hydrostatic pressure (Sugimoto, 2017). Knockout of PIEZO1 in osteoblasts and osteocytes blunts the skeletal response to mechanical loads and resulted in the impair of bone structure and strength (Li et al, 2019; Sun et al, 2019). And PIEZO1 agonist could increase bone mass in adult mice, simulating the effects of mechanical loading (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that coupling of Piezo1 with TRPV4 is responsible for the effects of high pressure in pancreatic acinar cells (28). If functional coupling between Piezo1-TRPV4 is a generalized process in which TRPV4 translates the mechanical force sensed by Piezo1 into pathological events, then other organ systems like urinary bladder and bone tissue where Piezo1and TRPV4 are coexpressed (21,(54)(55)(56)(57), may also be amenable to targeting Piezo1 or TRPV4 to prevent adverse effects of pressure or shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been verified that intracellular Ca 2+ concentration increases in cultured MSC after fluid flow stimulation (Riddle et al 2006;Stiehler et al 2009). Piezo type mechanosensitive ion channel component 1 (Piezo1) was been recently found to be crucial for bone formation (Tsimbouri et al 2017), and it is present in osteoblasts, osteocytes (Sun et al 2019) and MSCs (Sugimoto et al 2017). Piezo1 is activated by various forms of mechanical stimulation, including shear stress.…”
Section: Mechanosensitive Ion Channelsmentioning
confidence: 95%